Determination and Pharmacokinetic Profiles of Four Active Components From Scrophularia ningpoensis Hemsl. in Rats - Luo, Shunbin; Xie, Lingping; Chen, Jingjing; Tang, Congrong; Xu, Ren-ai (Frontiers in Pharmacology, 2021)
Acteoside, angoroside C, harpagoside, and cinnamic acid, which are the main bioactive ingredients of Scrophularia ningpoensis Hemsl., have wide clinical use with various biological effects. A new and sensitive ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was established with taxifolin as the internal standard (IS) in this study and was successfully used to study the pharmacokinetic profiles of four active components from Scrophularia ningpoensis Hemsl. in rats after sublingual intravenous administration. After protein precipitation with acetonitrile, the mobile phase (consisting of acetonitrile and 0.1% formic acid) was used to separate the analytes on an Acquity UPLC BEH C18 chromatography column (2.1 × 50 mm, 1.7 μm) under gradient elution. The precursor-to-product ion transitions of 623.4 → 161.3 m/z for acteoside, 783.5 → 175.0 m/z for angoroside C, 493.3 → 345.2 m/z for harpagoside and 147.2 → 103.4 m/z for cinnamic acid were monitored by mass spectrometry with negative electrospray ionization in multiple reaction monitoring (MRM) mode. The concentration range of 10-1000 ng/mL could be detected by this method with a lower limit of quantification (LLOQ) of 10 ng/mL for each analyte. The intra- and inter-day precision (RSD%) of the method ranged from 2.6 to 9.9% and 2.7 to 11.5%, respectively. Meanwhile, the accuracy (RE%) was -9.6 to 10.7% in this developed method. The mean recoveries of four active components from Scrophularia ningpoensis Hemsl. were more than 76.7% with negligible matrix effects. The four active components from Scrophularia ningpoensis Hemsl. were stable under multiple storage and process conditions. A new, sensitive and simple analytical method had been established and was successfully applied to the pharmacokinetic profiles of four active components from Scrophularia ningpoensis Hemsl. in rats after sublingual intravenous administration.